The determinants of economic growth in Malaysia (1983-2017) / Nurul Yasmin Syazwani A.Wahid - A.Wahid, Nurul Yasmin Syazwani (2018)
Economic growth is an indicator used by country in order to measure the economy performance either they are facing bad or good condition in the economy. A change in economy may occur anytime and can affect the development of the country. In addition, a positive image can be showed when the country having a good and stable condition, so that it's able to attract other countries to invest in the country. Hence, country's level of success can be measure from their economic growth or stability. Therefore, the purpose of this research study was to examine the determinants of economic growth in Malaysia by using yearly time series data from year 1983 until 2017. The multiple linear regression were used in this research study to analyse the significant relationship between the dependent variable which is gross domestic product (GDP) and the independent variables which are trade openness (TO), foreign direct investment (FDI), government expenditure (GE) and gross fixed capital formation (GFCF). The finding suggested that Malaysia's economic growth is determined by the changes in trade openness, foreign direct investment, government expenditure and gross fixed capital formation.